The Impact of Mindfulness-Based Stress Reduction on Emotional Wellbeing and Glycemic Control of Patients with Type 2 Diabetes Mellitus - A. Armani Kian; B. Vahdani; A. A. Noorbala; A. Nejatisafa; M. Arbabi; S. Zenoozian; M. Nakhjavani (Journal of Diabetes Research)
Objective. The aim of the study was to determine the effect of mindfulness-based stress reduction (MBSR) intervention on emotion regulation and glycemic control of patients with type 2 diabetes. Materials and Methods. Sixty patients with type 2 diabetes were recruited for this randomized controlled trial from an outpatient clinic at Imam Hospital in Iran. The intervention group participated in 8 sessions of MBSR, and the control group continued the treatment as usual. Fasting blood sugar and HbA1c were measured as two indices of glycemic control. Overall mental health, depression, and anxiety were measured using the General Health Questionnaire (GHQ-28), Hamilton Depression Rating Scale (HDRS), and Hamilton Anxiety Rating Scale (HARS), respectively. All the assessments were performed at baseline and after 8 weeks and 3 months as follow-up. Results. In comparison with the control group, the MBSR intervention group showed a significant reduction on all outcome measures including FBS, HbA1C, HARS, and HDRS scores (p<0/05). Conclusion. MBSR had a remarkable improvement on emotional wellbeing and glycemic control of patients with type 2 diabetes.